2017
DOI: 10.1016/j.tjem.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

A rare cause of acute abdomen in the ED: Chemotherapy-induced pneumatosis intestinalis

Abstract: Pneumatosis intestinalis (PI) and portomesenteric venous gas (PVG) refers to the presence of air within the intestinal wall and portomesenteric vessels. Most of the time, it is associated with mesenteric ischemia that requires immediate surgical intervention as it has high mortality rate. It may also be seen secondary to various conditions, including infections, surgeries, and some chemotherapeutic drugs. A 61-year old-male was admitted to our emergency department complaining of abdominal pain after chemothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Intestinal wall alteration and PVG may also be seen after chemotheraphy. 4 In our case, ileus was thought to have been caused by anticholinergic properties of drugs taken for chronic schizophrenia, which lead to bowel distention and bowel ischaemia, which caused intestinal wall alteration and PI, and finally PVGs. In the light of liberal use of CT, a larger portion of PVGs are found with variable prognosis.…”
Section: Images In…mentioning
confidence: 68%
“…Intestinal wall alteration and PVG may also be seen after chemotheraphy. 4 In our case, ileus was thought to have been caused by anticholinergic properties of drugs taken for chronic schizophrenia, which lead to bowel distention and bowel ischaemia, which caused intestinal wall alteration and PI, and finally PVGs. In the light of liberal use of CT, a larger portion of PVGs are found with variable prognosis.…”
Section: Images In…mentioning
confidence: 68%
“…All titles were screened, after which 65 full-text articles were assessed for eligibility. Ultimately, 50 records that met our eligibility criteria were identified, and 12 more reports were retrieved through reference mining, reaching a total of 62 articles that were included in our systematic review ( Figure 2 ) [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 62 , 64 , 65 , 67 , 68 , 69 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Among adult patients, secondary PI is mainly associated with gastrointestinal disease, pulmonary diseases, mechanical ventilation, endoscopic procedures, infections and other immunological conditions [ 8 ]. Medications used for cancer treatment are among the most recognized causes of PI, including cytotoxic chemotherapeutic agents [ 9 ] and molecular targeted agents [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…Six studies on steroid-related PI ( Galm et al, 2001 ; Han et al, 2002 ; Patel et al, 2014 ; Ozturk et al, 2017 ; Lee and Wu, 2019 ; Nunomiya et al, 2021 ) were included. Patient characteristics, medication therapies, treatments, prognosis, and outcomes are summarized in Table 1 .…”
Section: Literature Review Of Steroid-related Pi Casesmentioning
confidence: 99%
“…Patient characteristics, medication therapies, treatments, prognosis, and outcomes are summarized in Table 1 . Eight cases of PI secondary to the combined therapy of steroids and other cytotoxic, immunosuppressive agents ( Galm et al, 2001 ; Patel et al, 2014 ; Ozturk et al, 2017 ; Nunomiya et al, 2021 ) were identified, and two cases of PI secondary to steroid monotherapy ( Han et al, 2002 ; Lee and Wu, 2019 ). In addition, six patients had underlying hematopoietic and lymphoid system conditions ( Galm et al, 2001 ; Patel et al, 2014 ); one patient had lung adenocarcinoma, another had nasopharyngeal cancer ( Ozturk et al, 2017 ; Nunomiya et al, 2021 ), and the remaining two had nephrotic syndromes ( Han et al, 2002 ) and superior mesenteric artery syndromes ( Lee and Wu, 2019 ).…”
Section: Literature Review Of Steroid-related Pi Casesmentioning
confidence: 99%